Efektivitas Program Bantuan Langsung Tunai Dana Desa (BLT-DD) dalam Memutus Rantai Kemiskinan: Studi di Desa Gading Kecamatan Bululawang Kabupaten Malang - Hidayatur Rohmah; Luluk Dwi Kumalasari (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This study examines the effectiveness of the Direct Cash Assistance Program (BLT DD) in breaking the poverty chain in the village of Gading Bululawang, Malang. The BLT DD program is part of the government's efforts to break the poverty chain in Indonesia, especially in the Pandemic period. Every policy developed has positive and negative impacts in the implementation process. Based on the results of the field data collection, the community felt the BLT DD program helped meet their basic needs. The implementation of the program through several stages, namely determining names, cross checks, determination of names, and distribution of assistance. These steps are carried out transparently, with the participation of each hamlet head. Distribution of BLT DD assistance is done once a month. Over time, the distribution of assistance was hampered and the community did not understand the BLT DD program due to the lack of socialization of the village program. The method used in this study uses a qualitative approach with a type of case study. Research Subjects according to the criteria specified by researchers using purposive sampling techniques. Data collection in this study was carried out through observation, interview and documentation techniques. Based on the facts of field data and theoretical analysis by using the structural functionalism of Talcott Parson, the BLT DD program is considered to be quite useful to meet the basic needs of the community, but the community complained of a little delay given by the village. During the distribution process and lack of understanding of the support given so far. The results of the study resulted in the conclusion that the BLT DD program did not meet the effectiveness criteria because some indicators had not been met during the implementation process in the village of Gading Bululawang Malang